On German Orders. The Volhynian Massacre in Soviet Partisans’ Memoirs - Denys Shatalov (Connexe, 2020)
This paper is devoted to the analysis of the narrative displayed to the mass Soviet reader of the anti-Polish ethnic cleansing conducted by Ukrainian nationalists in 1943 in Volhynia. The sources used in this paper include the most widely published books of partisan commanders who were active in the region. These texts are examined as sources aimed to shape public opinion about the Ukrainian nationalists after the war. For the Soviet public, the memoirs of Soviet partisans operating in North-West Ukraine in 1943–1944 along with propagandist anti-nationalist literature were the main source of information about the Volhynian Massacre. In these books, the stories about the massacre appear, above all, to be a propaganda tool. The comparison of the depictions of the Volhynian Massacre provided by partisan authors with modern scholarly works shows us intentional distortions by the former. It may perhaps seem paradoxical to note that the partisan memoirists, who tended to discredit the Ukrainian nationalists, preferred to blame them only as perpetrators, but not as the initiators of the anti-Polish massacres in Volhynia. The anti-Polish “actions” were described primarily as a direct initiative of German occupational authorities, whereas the detachments of nationalists’ organisations were portrayed as its faithful executors. The memoirists stressed the disinterestedness and unwillingness of ordinary Ukrainian peasants to participate in the massacres and the alienation of its organizers from the broad masses of working people. In this light, the Soviet partisan memoirs give us little help in understanding the Volhynian massacre itself but serve as an excellent example of Soviet propaganda efforts aimed at modelling representations of the past.